Iterative receiver for the triple differential PSK modulation in the time-varying underwater acoustic communications - Cui, Hongyu; Liu, Changxin; Si, Boyu; Wu, Jie; Sun, Dajun (IET communications, 2020)
Due to the time-varying property of the underwater acoustic (UWA) channel, the significant Doppler spread will severely degrade the performance of direct-sequence spread-spectrum (DSSS) communications. The relative velocity variation between the transmitter and the receiver will cause both the phase rotation and the magnitude loss of correlation peak, during the long transmission of the DSSS packet. To solve this problem, the authors propose a novel transceiver design for the UWA DSSS communications. At the transmitter, the triple differential phase shift keying (D$^3$3PSK) modulation is adopted to overcome the phase rotation, whereas the phase noise will be amplified resulting in the signal-to-noise ratio (SNR) loss. At the receiver, the improved bit-interleaved coded modulation with iterative decoding algorithm for D$^3$3PSK is used to recover the SNR loss, in which the D$^3$3PSK demodulator is treated as the convolutional decoder, and the linear prediction is adopted to track the channel variation. Furthermore, an adaptive selection of local reference signal is also applied to recover the correlation loss. Theoretical simulation shows that the proposed transceiver can effectively mitigate the performance loss caused by the motion acceleration, and the performance gain is significant over the conventional.